Global Financial Risks, CVaR and Contagion Management - LIM, Kian Guan (Institutional Knowledge at Singapore Management University, 2012)
The September 2008 collapse of Lehman Brothers was the 9/11 on Wall Street, and many articles had been written on the changes in the global risk landscape that followed. However, there is scarcity of rigorous studies using empirical data and advanced econometric methods to verify such a change and the nature of such a change. In this paper, we provide rigorous analyses of statistically significant changes in global financial risks and sharp increases in conditional Value-at-Risk after September 2008. We perform statistical analyses using conditional distributions on the tail losses of equity portfolios constructed from the stock indexes of six major global financial markets. Employing the generalized marginal Pareto distribution and multivariate copula method, we provide strong empirical evidence to assert the prevalence of heightened global financial risks and its contagion effect across the globe. An important implication arising out of these conclusions is that banks under BASEL II and BASEL III and financial institutions in the near-future should not underestimate its Conditional Value-at-Risk by using the normal distribution model since under stressed situations past September 2008, the portfolio return distributions have tails that simultaneously grow longer and thinner in the direction of the loss region. We also provide some thoughts for contagion management.